Correlation of Index Finger Length (2D) with Height, Weight and BMI in Adult Bangladeshi Male - Hasan, Karim Rezwan; Ara, Shamim; Banna, Fakhrul Amin Mohammad Hasanul (Journal of Enam Medical College, 2017)
Background: Human hand is one of the most versatile parts of the human body which plays an important role in modern medical science and evolutionary biology. By virtue of evolution and genetic arrangements, digital lengths vary from person to person according to age, sex, races, occupation or even environmental influences. It has been found that the digital lengths and their ratios are not same in different sexes and even in both hands of same individual. Specially, index to ring digit lengths and their ratios which already have been proved to represent sexual dimorphism may differ in both hands of an individual and show positive correlations with other morphological attributes like height, weight and BMI. Objectives: To analyze the variation of index finger (2D) length and its correlation with height, weight and BMI in adult Bangladeshi male. Materials and Methods: This cross-sectional analytical study was conducted in the department of Anatomy, Dhaka Medical College, Dhaka from July 2012 to June 2013 on 100 male MBBS students (20?25 years of age). With the help of digital vernier caliper measurements of index finger length (2D) was recorded. Height and weight were measured by the stadiometer and weighing scale respectively. BMI was calculated from height and weight. Pearsons correlation analysis was done to find out the correlation of index finger length with height, weight and BMI. Results: Significant correlation has been found between the lengths of index fingers (2D) and height (p<0.01), but there was no significant correlation of index finger length with weight and BMI (p>0.05). Conclusion: In this study, we found variation in index finger lengths of both hands of Bangladeshi male subjects, which needs further study and comparison. J Enam Med Col 2017; 7(2): 90-94